Hubungan Autonomy-Supportive Teaching dengan Prokrastinasi Akademik Siswa SMA Jakarta yang menjalani Pembelajaran Jarak Jauh - Cita Aliviani; Niken Widi Astuti (Fakultas Psikologi Universitas Tarumanagara, 2022)
This study aims to determine the relationship between autonomy-supportive teaching and the academic procrastination of Jakarta high school students undergoing distance learning. Autonomy-Supportive Teaching is one of the learning methods in which the teacher understands the student's point of view by showing a desire to listen to students' opinions, providing opportunities for students to be able to choose and decide something related to activities in the classroom, and provide rational reasons when delivering material, giving assignments, or in setting a rule (Rohinsa et al., 2019). Meanwhile, academic procrastination is a tendency to delay school-related activities and behaviors (McCloskey & Scielzo, 2015). This research is a type of quantitative research using non-probability sampling techniques, namely purposive sampling and snowball sampling in online sampling. Participants in this study amounted to 169 high school students (SMA) Jakarta with an age range of 15-18 years. The measuring instruments used in this study were the Learning Climates Questionnaire (LCQ) to measure autonomy-supportive teaching and the Academic Procrastination Scale (APS) to measure academic procrastination. The results of this study indicate that autonomy-supportive teaching has a negative relationship with academic procrastination with a value of r = -.187 and p = .015. This means that the higher the autonomy-supportive teaching applied, the lower the academic procrastination carried out.